2001
DOI: 10.1182/blood.v98.12.3283
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 inhibits differentiation of hematopoietic cells by sustaining GATA-2 expression

Abstract: Notch signaling is involved in cell fate decisions in many systems including hematopoiesis. It has been shown that expression of an activated form of Notch1 (aNotch1) in 32D mouse myeloid progenitor cells inhibits the granulocytic differentiation induced by granulocyte colonystimulating factor (G-CSF). Results of the current study show that aNotch1, when expressed in F5-5 mouse erythroleukemia cells, also inhibits erythroid differentiation. Comparison of the expression levels of several transcription factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
86
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 47 publications
(47 reference statements)
11
86
0
Order By: Relevance
“…In T cells, inhibition of differentiation via suppression of pre-T-cell receptor expression has been suggested as a key mechanism of Notch-1-induced lymphomagenesis (Engel and Murre, 2002). Inhibition of differentiation may be mediated by Notch-induced helix-loop-helix inhibitory transcription factors and, in myeloid cells, by expression of GATA-2 (Kumano et al, 2001). Consistent with this multiplicity of biochemical mechanisms, different phenotypic effects are seen in different cell types.…”
mentioning
confidence: 71%
“…In T cells, inhibition of differentiation via suppression of pre-T-cell receptor expression has been suggested as a key mechanism of Notch-1-induced lymphomagenesis (Engel and Murre, 2002). Inhibition of differentiation may be mediated by Notch-induced helix-loop-helix inhibitory transcription factors and, in myeloid cells, by expression of GATA-2 (Kumano et al, 2001). Consistent with this multiplicity of biochemical mechanisms, different phenotypic effects are seen in different cell types.…”
mentioning
confidence: 71%
“…Most in vitro experiments have shown that active Notch-1 expands the stem cell compartment but blocks or delays terminal myeloid cell differentiation. Overexpression of constitutively active Notch-1 (ICN1) in 32D myeloid progenitor cell line inhibited granulocytic differentiation and permitted expansion of undifferentiated cells (22)(23)(24). This was probably mediated through RBP-J-Hes1 pathway since overexpression of Hes-1 had similar to ICN1 effect on 32D cell differentiation (23)(24)(25).…”
Section: Notch and Myeloid Cell Differentiationmentioning
confidence: 91%
“…This was probably mediated through RBP-J-Hes1 pathway since overexpression of Hes-1 had similar to ICN1 effect on 32D cell differentiation (23)(24)(25). ICN1 inhibited erythroid differentiation of F5-5 mouse erythrolekemia cells through sustained activity of GATA2 transcription factor (24). ICN1 also blocked differentiation of human myeloid cell line HL60 to granulocytes induced by all-trans retinoic acid (ATRA) or to monocytes induced by tetradecanoylphorbol acetate (TPA) (26,27).…”
Section: Notch and Myeloid Cell Differentiationmentioning
confidence: 98%
See 1 more Smart Citation
“…Specifically in the eyes, retinal SP cells have been reported to exhibit a high expression of nestin mRNA [32]. Notch 1 has also been frequently correlated to a stem cell-like phenotype, by delaying stem cell differentiation via the enhancement of self-renewal in both hematopoietic [33,34] and neural stem cells [35]. The higher expression of notch 1 observed in limbal epithelial SP cells suggests that these cells may indeed resemble other adult stem cells and may indicate a key role of notch 1 signaling in regulating ocular surface homeostasis through well-controlled corneal epithelial turnover.…”
Section: Discussionmentioning
confidence: 99%